Comparison of clinical features and pregnancy outcomes in early- and late-onset preeclampsia with HELLP syndrome: a 10-year retrospective study from a tertiary hospital and referral center in China - Boya Li; Huixia Yang (BMC, 2022)
Abstract Background Early-onset preeclampsia (EO-PE) and late-onset preeclampsia (LO-PE) are different subtypes of preeclampsia. We conducted this study to analyze the similarities and differences in the clinical features and pregnancy outcomes in EO- and LO-PE with HELLP syndrome. Methods This was a retrospective study in a tertiary hospital. Eighty-three parturients with HELLP syndrome were allocated into two groups based on the timing of preeclampsia onset: EO-PE with HELLP (n = 47) and LO-PE with HELLP (n = 36). Results In total, 31.9% and 63.9% of women in the EO-PE with HELLP and LO-PE with HELLP groups, respectively, were asymptomatic at diagnosis (P = 0.004, OR = 0.265 (0.106-0.662)). Headache or visual symptoms were more frequent in the EO-PE group than in the LO-PE group (48.9% vs. 25%, P = 0.026, OR = 0.348 (0.135-0.896)). Women in the EO-PE with HELLP group had higher SBP and DBP than those in the LO-PE with HELLP group. Laboratory tests, including platelets, liver function, and hemolysis, which are the main indicators for the diagnosis of HELLP syndrome, showed almost no significant differences between the two groups, with kidney function being the only difference observed. Women in the EO-PE with HELLP group had higher Scr than those in the LO-PE with HELLP group. The degree of proteinuria was higher in the EO-PE group than in the LO-PE with HELLP group. The incidence of severe maternal complications was significantly higher in the EO-PE group than in the LO-PE with HELLP group (25.5% vs. 5.6%, P = 0.016, OR = 0.172 (0.036-0.824)). In total, 57.4% and 8.3% of neonates in the EO-PE and LO-PE with HELLP groups were admitted to the NICU, and the difference was statistically significant, even after adjustment for the delivery week (P = 0.009, OR = 0.830 (0.729-0.944)). Postpartum HELLP syndrome was more common in the LO-PE group than in the EO-PE group (30.6% vs. 4.3%, P = 0.001, OR = 9.9 (2.031-48.256)). Conclusions Compared with LO-PE with HELLP patients, EO-PE with HELLP patients have more obvious kidney damage, higher blood pressure and a higher risk of adverse maternal and neonatal outcomes. Patients with LO-PE need to be alerted to the occurrence of HELLP syndrome after delivery.